Determining the drivers of continued mobile food delivery app (MFDA) usage during a pandemic period - Monique Munday; Michael Humbani (Cogent Business & Management, 2024)
AbstractThe study aimed to determine the main factors that predicted users’ intention to continue using mobile food delivery apps during the COVID-19 pandemic. The moderating role of user experience was also explored. Data were obtained from 411 users of mobile food delivery apps in South Africa, using the purposive sampling technique. The lens of the integrated modified unified theory of acceptance and use of technology (UTAUT2) and the task technology fit (TTF) were used for this research. The results indicate that users’ continuance intentions are influenced by performance expectancy and habit, and that hedonic motivation and TTF are insignificant predictors. Performance expectancy mediates between TTF and continuance intention, and user experience moderates the relationship between predictors (TTF, hedonic motivation, habit) and continuance intention. Restaurant owners can use the findings of this study to design winning strategies that mix both technology features and mental perceptions to build a stronger client base during crises and future business possibilities.